2019
DOI: 10.5937/jaes17-22032
|View full text |Cite
|
Sign up to set email alerts
|

Engineering method of fault-tolerant system simulations

Abstract: It is shown that common method of units failure compensation, based on an introduction to the system a structural redundancy, leads to the increase of weight/size factor and energy consumption, but sometime does not prolongs its lifetime. The new approach to fault/recovery process modeling, based on use of fundamental apparatus of parallel semi-Markov process, in which ordinary processes simulate the life-cycle of individual units, and the complex process, assembled from ordinary processes, simulates reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Each of these elements can randomly be in different states that affect the state of the entire system. At the stage of designing electric power systems, it is important to determine the indicators of structural reliability of [24][25][26] elements. In practice, probabilistic models can be used for this, in particular, Markov and semi-Markov models [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these elements can randomly be in different states that affect the state of the entire system. At the stage of designing electric power systems, it is important to determine the indicators of structural reliability of [24][25][26] elements. In practice, probabilistic models can be used for this, in particular, Markov and semi-Markov models [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed a model to characterize the problem and used simulation to study the shipment policy's impact on planning the fabrication-maintenance-shipment. Other studies [5][6][7][8][9][10][11][12] addressed the impact of different imperfect fabrication processes and their consequent actions on productioninventory planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their study suggested some managerial insights to facilitate better decision-making. Other studies [27][28][29][30][31][32][33][34][35][36][37][38] investigated the influence of distinct imperfect features on production processes and their subsequent corrective actions, and a multi-item, multistage decision model (including generic materials and operations planning) on the operating policy of various supply-chain and fabrication planning, operations, and management. As few past studies have concentrated on exploring the collective and individual impact of product commonality, adjustable-rate, postponement, and rework on multi-item manufacturing decision-making, this study aims to specifically address the aforementioned subject.…”
Section: Introductionmentioning
confidence: 99%